Computation of scattering matrix elements of large and complex shaped absorbing particles with multilevel fast multipole algorithm. (May 2015) - Wu, Yueqian; Yang, Minglin; Sheng, Xinqing; Ren, Kuan Fang
Abstract: Light scattering properties of absorbing particles, such as the mineral dusts, attract a wide attention due to its importance in geophysical and environment researches. Due to the absorbing effect, light scattering properties of particles with absorption differ from those without absorption. Simple shaped absorbing particles such as spheres and spheroids have been well studied with different methods but little work on large complex shaped particles has been reported. In this paper, the surface Integral Equation (SIE) with Multilevel Fast Multipole Algorithm (MLFMA) is applied to study scattering properties of large non-spherical absorbing particles. SIEs are carefully discretized with piecewise linear basis functions on triangle patches to model whole surface of the particle, hence computation resource needs increase much more slowly with the particle size parameter than the volume discretized methods. To improve further its capability, MLFMA is well parallelized with Message Passing Interface (MPI) on distributed memory computer platform. Without loss of generality, we choose the computation of scattering matrix elements of absorbing dust particles as an example. The comparison of the scattering matrix elements computed by our method and the discrete dipole approximation method (DDA) for an ellipsoid dust particle shows that the precision of our method is very good. The scattering matrix elements of large ellipsoid dusts with different aspect ratios and size parameters are computed. To show the capability of the presented algorithm for complex shaped particles, scattering by asymmetry Chebyshev particle with size parameter larger than 600 of complex refractive index m = 1.555 + 0.004 i and different orientations are studied. Abstract : Highlights: Computation of scattering matrix of large absorbing non-spherical particle is presented. Multilevel Fast Multipole Algorithm is proved and parallelized with hybrid MPI and OpenMP. Calculable size parameter can be as large as 628 for refractive index m = 1.555 + 0.004 i . Results of spheroidal and ellipsoidal particles and Chebyshev particle are exemplified.